Consequences of Land-use Changes on Ecology of Arid Zone of Rajasthan - Gajja, B L; Parihar, R P (Annals of Arid Zone, 2016)
Analysis of secondary data on land use pattern from 1960-61 to 1993-94 suggested that the area under forest, permanent pasture and grazing, and miscellaneous trees and groves should be increased to improve the ecological condition of the region. Cultivation on the land not suitable for it not only threatens sustainability and ecology of the region, but also lowers the agricultural productivity. It is appropriate to use such lands for forestry and pastures development to improve the fertility of the soils.